The prevalence of tic disorders in children and adolescents in Brazil - Helvio L. Alves; Elizabeth M. A. B. Quagliato (Arquivos de Neuro-Psiquiatria)
Tourette syndrome (TS) and tic disorders represent events of familiar magnitude characterized by involuntary movements and/or vocalization. To determine the prevalence of TS/tic disorders we studied a sample of 762 subjects (388 M, 374 F), between 1992 and 1997, age 6 to 43 years old, taken out of a population of 10,155 subjects (4,918 M, 5,237 F; age: 3-56 years old). A structured 4-item questionnaire, direct interview (multistaged), >1 yr follow-up, were used. 9,565 subjects (4,614 M, 4,951 F) sent back the questionnaires, 3,354 of these (1,671 M, 1,683 F) with positive answers to tics. 42 subjects (31 M, 11 F, age: 7-21 years old, mean: 11 years old) met the DSM-III-R criteria. The total minimal prevalence of TS is 0.43%, with a 3:1 ratio male/female. The minimal prevalence of chronic tic disorder is 2.27%. The total minimal prevalence for tic disorders at all is 2.91%. No special education students participation.